2020
DOI: 10.1055/s-0040-1721708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Feline Bone Surrogate and In Vitro Mechanical Comparison of Small Interlocking Nail Systems in Mediolateral Bending

Abstract: Objective The aim of this study was to (1) evaluate bending structural properties of a machined short fibre epoxy (SFE) feline bone surrogate (FBS), (2) compare the bending behaviour of small angle-stable interlocking nails (I-Loc; Targon) and locking compression plates (LCP) and (3) evaluate the effect of implant removal on FBS bending strength. Methods Part 1: Feline cadaveric femurs (n = 10) and FBS (n = 4) underwent cyclic four-point bending and load to failure. Part 2: Fracture gap FBS construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…There are benefits and limitations of ILN or LCP use (20)(21)(22). Although the LCP counteracted bending and torsion to a similar degree as the ILN-10, some intricacies of LCP placement require consideration and might make them less suitable implants for a particular situation.…”
Section: Discussionmentioning
confidence: 99%
“…There are benefits and limitations of ILN or LCP use (20)(21)(22). Although the LCP counteracted bending and torsion to a similar degree as the ILN-10, some intricacies of LCP placement require consideration and might make them less suitable implants for a particular situation.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size (n = 5 printed models humerus/printer type) was based on previous studies using 3D printed or machined bone models. 32,[36][37][38][39] Normality of data distribution was evaluated using the Shapiro-Wilk test. Mean dimension differences between groups were compared using a two-factor (bone size and printer type) repeated measures ANOVA followed by Tukey post-hoc tests when significant differences were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size ( n = 5 printed models humerus/printer type) was based on previous studies using 3D printed or machined bone models 32,36–39 . Normality of data distribution was evaluated using the Shapiro–Wilk test.…”
Section: Methodsmentioning
confidence: 99%
“…By comparison, the I-Loc system does not allow correction of alignment after placement of the locking bolts but may be mechanically superior and is appropriate for use in metaphyseal fractures. Ex vivo studies of the I-Loc system provide evidence that the I-Loc 3 and I-Loc 4 nails have greater torsional stability compared with size-matched TVS nails and small (2.0 mm and 2.4 mm) LCPs, 89 that the I-Loc 4 provides more bending stability than the sizematched TVS nail 91 and that the I-Loc system may be associated with a lower risk of post-explantation refracture than TVS nails. 89,91 In addition, clinical studies have reported the use of the I-Loc system in a wide variety of feline fracture configurations with good outcomes.…”
Section: Jfms Clinical Practice 453mentioning
confidence: 99%
“…Ex vivo studies of the I-Loc system provide evidence that the I-Loc 3 and I-Loc 4 nails have greater torsional stability compared with size-matched TVS nails and small (2.0 mm and 2.4 mm) LCPs, 89 that the I-Loc 4 provides more bending stability than the sizematched TVS nail 91 and that the I-Loc system may be associated with a lower risk of post-explantation refracture than TVS nails. 89,91 In addition, clinical studies have reported the use of the I-Loc system in a wide variety of feline fracture configurations with good outcomes. 81,92 It should be noted that interlocking nails can be placed without the need for fluoroscopy as palpation of anatomical landmarks while flexing and extending the leg has been shown to be accurate for limb alignment; 22 Although external skeletal fixators are particularly well suited to non-reconstructable fractures, they can be applied to all fracture types.…”
Section: Jfms Clinical Practice 453mentioning
confidence: 99%